Security vetting in the Department of Home Affairs - Molapo, Kgaugelo (My University, 2017)
This is a report on Security Vetting in the Department of Home Affairs. The South African Public Service (including the Department of Home Affairs) as an employer has an obligation to deliver services in an accountable and transparent manner and because of that people who obtain employment in the public sector are expected to possess a high level of integrity and professional ethics. The Security Screening Investigation (SSI) commonly known as Security Vetting or Vetting was introduced in government departments with the objective of ensuring that all the individuals employed in government with access to classified information possess the qualities that will enable them “not to cause classified information or material to fall into unauthorised hands, thereby harming or endangering the security and/or interests of the State”. The process of vetting is, however, the mandate of the State Security Agency (SSA), with the responsibility of a larger portion of the vetting process while the smaller portion of the function lies with some government departments, of which the DHA is one. It has been observed that regardless of the decentralization of the functions of vetting by the SSA, there are still challenges that are experienced in DHA with the current vetting approach/strategy. This study was undertaken with the purpose of identifying and describing the challenges relating to the current vetting process in the DHA and as a follow-up to determine the possibility of establishing a strategy that will address the current shortcomings. Interviews were undertaken with Home Affairs officials to collect data on the effectiveness and efficiency of the current vetting strategy in the department, the challenges and the shortcomings concerning vetting, as well as how vetting strategy can be constructed in order to alleviate the challenges and the shortcomings. The findings indicate that the current vetting strategy is neither effective nor efficient. The report further indicates that there are several challenges with the current vetting strategy in DHA, such as DHA reliance on SSA for the completion of the vetting process, a shortage of vetting officers in the department, delayed turnaround times on the conclusion of the vetting process as well as failure in the implementation of the vetting strategy. The conclusion is that the current vetting strategy needs to be reviewed and improved.
Mini-thesis submitted in fulfilment of the requirements for the Degree of Masters of Management in the field of Security (MM-S) In the Graduate School of Public and Development Management University of Witwatersrand February 2017
Keywords: Civil service--South Africa--Personnel management; Employee screening--South Africa; Security systems--South Africa